Prevention of sudden cardiac death in childhood-onset hypertrophic cardiomyopathy. (September 2021) - Kaski, Juan Pablo; Norrish, Gabrielle
Abstract: Background: Sudden cardiac death (SCD) is the most common cause of death in children with HCM. Although recent population-based studies have shown that SCD rates are lower than previously thought, it still occurs more frequently than in adult patients, highlighting the importance of accurate identification of those at risk. Aim of Review: This review highlights risk factors for SCD in childhood HCM, current risk stratification guidelines, and novel personalized models for risk prediction. Key Scientific Concepts of Review: The traditional approach to risk prediction in childhood-onset HCM, using cumulative risk factor thresholds and adopted by current international guidelines, has involved extrapolation of adult data, but recent evidence has demonstrated that this approach does not accurately discriminate high-risk from low-risk individuals. In response to this knowledge gap, novel pediatric-specific risk stratification models have been developed that allow calculation of individualized estimates of SCD risk and enable a personalized and shared decision-making approach to ICD implantation. Highlights: Sudden cardiac death (SCD) is the commonest cause of death in childhood hypertrophic cardiomyopathy (HCM) Current risk stratification algorithms have poor discriminatory ability in children with HCM The HCM Risk-Kids SCD risk prediction model provides individualised 5 year SCD risk estimates (https://hcmriskkids.org ) Future work to refine these models with the addition of novel risk factors is required